Border Crossings: Dialogue Across and Within Fields and Traditions - Vokey, Daniel (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
Drawing upon the work of Chantal Mouffe, Alasdair MacIntyre, and Bernard Lonergan, in this paper I develop an argument that, in our work as philosophers of education, we should support a particular form of what Ernst Boyer has termed the scholarship of integration, in part by being explicit both about the tradition(s) of inquiry in which we are working and about the nature of the particular contribution(s) we hope to make to those traditions. It offers five reasons why we should support systematic, sympathetic, agreement-oriented assessments of competing worldviews and corresponding ways of life. It advocates two kinds of “border crossings” as integral to such assessment: engagement across disciplines and fields on the one hand, engagement with rival paradigms within a discipline or field on the other.